Canon EOS Rebel T5i/700D : from snapshots to great shots - Revell, Jeff (Peachpit Press, 2014)
Now that you've bought the amazing Canon EOS Rebel T5i / 700D, you need a book that goes beyond a tour of the camera's features to show you exactly how to use the camera to take great pictures. With Canon EOS Rebel T5i / 700D: From Snapshots to Great Shots, you get the perfect blend of photography instruction and camera reference that will take your images to the next level! Beautifully illustrated with large, vibrant photos, this book teaches you how to take control of your photography to get the image you want every time you pick up the camera. Follow along with your friendly and knowledgeable guide, photographer and author Jeff Revell, and you will: Learn the top ten things you need to know about shooting with the Rebel Use the Rebel's automatic modes to get better shots right away Move on to the Creative zone, where you have full control over the look and feel of your images Master the photographic basics of composition, focus, depth of field, and much more Learn all the best tricks and techniques for getting great action shots, landscapes, and portraits Find out how to get great shots in low light Fully grasp all the concepts and techniques as you go, with assignments at the end of every chapter And once you've got the shot, show it off! Join the book's Flickr group, share your photos, and discuss how you use your Rebel to getgreat shots at flickr.com/groups/t5i700dfromsnapshotstogreatshots.